Skeptisme Profesional, Independensi dan Pengungkapan Kecurangan: Studi pada Hotel di Kabupaten Badung - Mertanaya, I Putu Eka; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p14, 2020)
Good fraud disclosure occurs when the internal supervisor as an auditor has aspects that support the fraud disclosure process. This study aims to determine the effect of professional skepticism and independence on fraud disclosure. This research was conducted at 3-star hotels and above in South Badung Regency with a total of 11 participating hotels. The technique used is purposive sampling technique which is included in nonprobability sampling. Data collection methods by conducting questionnaires and data analysis methods using multiple linear regression methods. The results of this study indicate that professional skepticism has no significant effect on disclosure of fraud and independence has a significant effect on disclosure of fraud. The lack of skepticism internal supervisors have due to mutual trust with coworkers. Both private and state companies, the auditors in a company still maintain its independence in conducting the audit process. Keywords: Professional Skepticism; Independence; Fraud Disclosures.